A Proposal of Human Interactive Proof in the Text Domain - Ximenes, Pablo; Santos, André dos; Fernandez, Marcial; Celestino Jr., Joaquim (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2005: Anais do V Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2005.21543, 2005)
This work describes a proposal for a novel type of Human Interactive Proof based on natural language Artificial Intelligence problems. It is a test to tell humans and computers apart that requires only plain text to be assembled. Although this is a work in progress, this paper shows the real feasibility of constructing such a Human Interactive Proof.